2015
DOI: 10.1371/journal.pntd.0003882
|View full text |Cite
|
Sign up to set email alerts
|

Three Gorges Dam: Impact of Water Level Changes on the Density of Schistosome-Transmitting Snail Oncomelania hupensis in Dongting Lake Area, China

Abstract: BackgroundSchistosomiasis remains an important public health issue in China and worldwide. Oncomelania hupensis is the unique intermediate host of schistosoma japonicum, and its change influences the distribution of S. japonica. The Three Gorges Dam (TGD) has substantially changed the ecology and environment in the Dongting Lake region. This study investigated the impact of water level and elevation on the survival and habitat of the snails.MethodsData were collected for 16 bottomlands around 4 hydrological st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 20 publications
0
30
2
Order By: Relevance
“…Dams can alter water flow, sediment flow, and the overall typology of downstream environments [65] causing major ecological alteration in the habitats of humans and aquatic organism diversity [66]. For example, Wu et al [67] looked at how differences in water level and water quality parameter fluctuation impacted the density of schistosoma-transmitting snails, Oncomelania hupensis , in Dongting Lake, located near the Three Gorges Dam. They found that low elevation sites saw slight increases of snail density after the completion of the dam, possibly in relation to changes in water temperature, hydrology, vegetation, soil and more indirectly salinity and nitrogen content [67].…”
Section: Discussionmentioning
confidence: 99%
“…Dams can alter water flow, sediment flow, and the overall typology of downstream environments [65] causing major ecological alteration in the habitats of humans and aquatic organism diversity [66]. For example, Wu et al [67] looked at how differences in water level and water quality parameter fluctuation impacted the density of schistosoma-transmitting snails, Oncomelania hupensis , in Dongting Lake, located near the Three Gorges Dam. They found that low elevation sites saw slight increases of snail density after the completion of the dam, possibly in relation to changes in water temperature, hydrology, vegetation, soil and more indirectly salinity and nitrogen content [67].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this study supports the view that the building of the TGD is expected to increase the schistosomiasis transmission (McManus et al 2010). However, researches that are more recent indicated that the construction of the TGD has no impact, or even a positive one, on prevention of schistosomiasis (Gray et al 2012;Li et al 2013;Zhu et al 2013;Chen et al 2014;Wu et al 2015). In comparison with these studies, the distinct results might have been caused by different study methods, including differences in data source, research object, study area, and study time period.…”
Section: Discussionmentioning
confidence: 97%
“…In particular, the relative abundance of Bsg snails was found to be negatively correlated with that of Filopaludina martensi martensi snails, further underscoring the possible influence of species interaction on Bsg snail population and the potential effect of anthropogenic irrigation practices on Bsg snail ecology [18]. The influence of agricultural practices on water quality parameters resulting in changes in the ecology of intermediate hosts has also been shown for several other helminthes of public health significance, including schistosomes [19]. …”
Section: Embracing Complexity For Liver Fluke Sustainable Controlmentioning
confidence: 96%